INTEGRATION OF “CLIL” IN TEACHING A FOREIGN LANGUAGE AS A MODERN VECTOR OF LANGUAGE EDUCATION DEVELOPMENT (TAMADDUN NURI JURNALI, 2025)
The article examines specificity of the CLIL (Content and Language Integrated Learning), a modern innovative method of foreign language teaching. Special attention is paid to the use of the CLIL while teaching English to preschool children. The basic principles of the CLIL are analysed and its advantages when teaching a foreign language are shown. The forms of implementing the CLIL while teaching English to preschool children are revealed.